Buckwheat containing-bread: a scientific inquiry into insulin, polyphenols, antioxidants status, and oxidative stress markers in type-II diabetic individuals - Begum, Khoula; Khan, Imran; Wali, Asif; Sami, Rokayya; Aljumayi, Huda; Abushal, Suzan A.; Algheshairy, Reham M.; Alharbi, Hend F.; Tayeb, Faris J.; Alharbi, Zeyad M.; Al-Eisa, Rasha A.; Almehmadi, Awatif M.; et al. (Frontiers in Sustainable Food Systems, 2024)
Buckwheat grains contain bioactive components with known effects on cardio-metabolic biomarkers. Previous research on oxidative stress markers made exclusively from wheat flour or two-hour postprandial levels of antioxidant status, plasma total polyphenols, and advanced glycation end products (AGEs) were considerably higher than fasting values after consuming buckwheat-incorporated bread (BWB), including clinical, animal, and epidemiological studies, suggesting the potential of buckwheat intake to influence parameters such as polyphenol intake, antioxidant status, insulin levels, and oxidative stress markers. However, the specific impact of buckwheat-containing bread on these biomarkers in individuals with type-II diabetes remains a significant gap in our understanding. Our current work aims to address this gap by exploring the effects of buckwheat-containing bread on insulin levels, polyphenol intake, antioxidant status, and markers of oxidative stress. In a randomized crossover study, 16 individuals with type-II diabetes were assigned to consume control bread made exclusively from wheat flour or bread incorporating 50% buckwheat flour. The research followed a crossover design, with a period of one to two washout interventions. Test breads were given at breakfast following a 12 h fast the previous night. After 2 h of bread intake, blood samples were collected at baseline (fasting). The two-hour postprandial levels of antioxidant status, plasma total polyphenols, and advanced glycation end products (AGEs) were significantly higher than fasting values after consuming buckwheat-incorporated bread (BWB). This suggests that the buckwheat-containing bread improved plasma total polyphenol levels and total antioxidant status. Our research concludes that the intake of bread containing buckwheat positively influences polyphenols in plasma and the status of antioxidants. This suggests that incorporating buckwheat into bread may have favorable effects on biomarkers associated with cardio-metabolic health in individuals with type-II diabetes. By addressing these knowledge gaps, our research aims to inform and engage the scientific community in further exploration of the potential health benefits of buckwheat-containing bread.